2009
DOI: 10.1101/gr.095299.109
|View full text |Cite
|
Sign up to set email alerts
|

BayesCall: A model-based base-calling algorithm for high-throughput short-read sequencing

Abstract: Extracting sequence information from raw images of fluorescence is the foundation underlying several high-throughput sequencing platforms. Some of the main challenges associated with this technology include reducing the error rate, assigning accurate base-specific quality scores, and reducing the cost of sequencing by increasing the throughput per run. To demonstrate how computational advancement can help to meet these challenges, a novel model-based base-calling algorithm, BayesCall, is introduced for the Ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
103
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(103 citation statements)
references
References 10 publications
0
103
0
Order By: Relevance
“…The bias in the distributions of fluorescence intensities appears in later sequencing cycles, which can be alleviated by an intensity normalization [171]. A number of improved base callers have been developed to reduce the error rate for each platform, including Rsolid [171] for the SOLiD platform, Pyrobayes [172] for the 454 platform, and BayesCall [173], Ibis [174], Seraphim [175], and AYB [176] for the Illumina platform. Base-calling algorithms use quality scores to estimate error probabilities for each base call, most of which can be transformed to Phred quality score (Q) [177].…”
Section: Bioinformatics Challenges and Solutionsmentioning
confidence: 99%
“…The bias in the distributions of fluorescence intensities appears in later sequencing cycles, which can be alleviated by an intensity normalization [171]. A number of improved base callers have been developed to reduce the error rate for each platform, including Rsolid [171] for the SOLiD platform, Pyrobayes [172] for the 454 platform, and BayesCall [173], Ibis [174], Seraphim [175], and AYB [176] for the Illumina platform. Base-calling algorithms use quality scores to estimate error probabilities for each base call, most of which can be transformed to Phred quality score (Q) [177].…”
Section: Bioinformatics Challenges and Solutionsmentioning
confidence: 99%
“…Base calling was done using Illumina Bustard (Kao et al 2009) and quality control with FastQC (http://www.bioinformatics. babraham.ac.uk/projects/fastqc/).…”
Section: Dna Samples Sequencing and Data Processingmentioning
confidence: 99%
“…There are two main approaches to addressing this challenge: (1) One approach is to develop improved image analysis and base-calling algorithms. This line of work has been pursued by several researchers in the past, including ourselves (for review, see Erlich et al 2008;Rougemont et al 2008;Kao et al 2009;Kircher et al 2009;Whiteford et al 2009; Kao and Song 2011). Indeed, by using more sophisticated statistical methods, it has been demonstrated that it is possible to deliver significant improvements over the tools developed by the manufacturers of the sequencing platforms.…”
mentioning
confidence: 99%